Pelatihan Proses Pembuatan Film Pendek sebagai Media Dakwah Siswa-Siswi SMA Nurul Ikhlas Kabupaten Tanah Datar - Ana Citra Annisa; Anandita Yahya; Fajar Indayani; Ginna Syofany (Lembaga Yasin AlSys, 2026)
The development of digital technology has encouraged the use of audiovisual media as an innovative learning tool, one of which is short films that can convey messages effectively and engagingly. However, students’ ability to produce short films remains limited, both in technical and conceptual aspects, so structured training is needed. This activity aims to describe the form of training used to improve the understanding, skills, and creativity of students at SMA Nurul Ikhlas, Tanah Datar Regency, in the process of making short films while also utilizing them as a medium of da’wah. This activity used a participatory descriptive approach through survey and training implementation stages. The survey stage was conducted to identify students’ interests and needs, while the implementation stage included lectures, question-and-answer sessions, and practical activities. The training materials covered determining story ideas, scriptwriting, the production process, and editing. The results of the activity showed a significant improvement in students’ understanding of storytelling concepts, technical skills in film production, and creativity. In addition, this activity had a positive impact on the development of soft skills, such as teamwork, communication, and critical thinking. Students’ enthusiasm and motivation also increased, as reflected in their active involvement throughout the training process. The conclusion of this activity emphasizes that short film production training can serve as an effective alternative to project-based learning, is relevant to educational needs in the digital era, and has the potential to function as a creative and educational da’wah medium for the younger generation.